Percepción del estudiantado universitario sobre la virtualización de la enseñanza de la metodología de la investigación científica en la educación superior - Vega Umaña, Lhiam; Barrantes Aguilar, Luz Elena (Universidad de Costa Rica, 2022)
The COVID-19 pandemic involved the construction and reconstruction of educational scenarios, among these processes the implementation of education modalities other than traditional face-to-face stands out. The objective of the article was to analyze the incidence of the variables age, sex and previous knowledge in research on the preference of the student body over the face-to-face or virtual modality. The working hypothesis is that there is a relationship between these variables and the student's preference for a certain teaching modality. Virtuality is understood as the use of technological tools, digital platforms and virtual classrooms in training processes. The study is based on a quantitative approach, a cross-sectional non-experimental design with a correlational scope is executed. We worked with a sample of 295 students enrolled in bachelor's degree during the III cycle, 2021 (September – December), at the headquarters of the Florencio del Castillo University (UCA), Cartago, Costa Rica. The results indicate that, in all cases, students prefer the virtual modality over the presence, but of the three variables contrasted: career, age and gender, only the career to which they belong showed statistically significant differences in preference. Most of these people claim to have very little or no knowledge in academic research, although they have conducted research in the courses of their careers, and do not know the institutional model for the preparation of final graduation papers (TFG), thesis modality. These variables have a statistically significant relationship with the career in which they are enrolled. Finally, approximately half of the people consulted consider that the communication received on these topics by their careers is very bad or bad, which allows to identify an aspect of improvement in the management of careers and in the training processes linked to academic research. It is important to investigate, in future studies, these variables from a qualitative approach for the case of teaching staff. It is concluded that the perception of university students about the virtualization of the teaching of the research methodology is positive. In this context, the variables age, sex and previous research knowledge do not determine their preference for virtuality.